How to select patients requiring coronary revascularisation using coronary physiology - Modi, Bhavik (JRSM Cardiovasc Dis, 2021)
The coronary angiogram is an indicator of flow limiting coronary artery disease but coronary physiology at the time of angiography is vital in assessing the true functional significance of coronary artery disease. With advances in guidewire technology and the greater use of physiology within the catheter laboratory, there is now a slow evolution of physiological indices in being able to reliably assess the functional significance of individual lesions and also the adequacy of revascularization in a growing range of clinical scenarios. As co-registration of physiology with the angiogram and intravascular imaging will become easier, we will find ourselves increasingly in an era of ‘Precision PCI’.